Pemanfaatan Daun Kelor sebagai Alternatif Produk Unggulan Di Desa Murtajih, Kecamatan Pademawu, Kabupaten Pamekasan - Aliftasya Silvy Agustina; Isma Karunia Dewi; Ahmad Irsyad Amru Rosyidi; Nur Muhammad Fanani; Purnamasari, Dian Neipa (Jurnal Insan Pengabdian Indonesia, 2025)
Moringa leaves (Moringa oleifera) are one of the most extraordinary plants ever found, and scientiﬁcally Moringa leaves are a source of nutrients that are diﬀerent from plants in general. Most people do not understand the potential that exists around Murtajih Village, such as the moringa plants that grow a lot in the community's yard. The aim is to increase public knowledge about the utilization of village potential in the form of Moringa leaves. It is hoped that the PKK mobilizing group in Murtajih Village, which has participated in the socialization, will be able to distribute the information that has been obtained to the surrounding community and be able to experience the beneﬁts optimally in the development of UMKM in Murtajih Village.